Clinical features and psychiatric comorbidities of borderline personality disorder patients with versus without a history of suicide attempt. (30th December 2016) - Sher, Leo; Fisher, Amanda M.; Kelliher, Caitlin H.; Penner, Justin D.; Goodman, Marianne; Koenigsberg, Harold W.; New, Antonia S.; Siever, Larry J.; Hazlett, Erin A.
Abstract: Patients with borderline personality disorder (BPD) are at high risk for suicidal behavior. However, many BPD patients do not engage in suicidal behavior. In this study, we compared clinical features of BPD patients with or without a history of suicide attempts and healthy volunteers. Compared with healthy volunteers, both BPD groups had higher Affective Lability Scale (ALS), ALS – Depression-Anxiety Subscale, Barratt Impulsivity Scale (BIS), and Lifetime History of Aggression (LHA) scores and were more likely to have a history of temper tantrums. BPD suicide attempters had higher ALS, ALS – Depression-Anxiety Subscale and LHA scores and were more likely to have a history of non-suicidal self-injury or temper tantrums compared to BPD non-attempters. Also, BPD suicide attempters were more likely to have a history of comorbid major depressive disorder and less likely to have comorbid narcissistic personality disorder (NPD) in comparison to BPD non-attempters. About 50% of study participants in each BPD group had a history of comorbid substance use disorder (SUD). Our study indicates that BPD patients with a history of suicide attempt are more aggressive, affectively dysregulated and less narcissistic than BPD suicide non-attempters. Highlights: BPD suicide attempters had higher affective lability compared to BPD non-attempters. BPD suicide attempters were more likely to have a history of comorbid MDD. BPD suicide attempters were less likely to have comorbid narcissistic PD. BPD suicide attempters are more severely mentally ill than BPD non-attempters.